1986
DOI: 10.1172/jci112723
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor in normal subjects and heart failure patients. Plasma levels and renal, hormonal, and hemodynamic responses to peptide infusion.

Abstract: We investigated atrial natriuretic factor (ANF) in humans, measuring plasma immunoreactive (ir) ANF (in femtomoles per milliliter), and renal, hormonal, and hemodynamic responses to ANF infusion, in normal subjects (NL) and congestive heart failure patients (CHF). Plasma irANF was 11±0.9 fmol/ml in NL and 71±9.9 in CHF (P < 0.01); the latter with twofold night ventricular increment (P < 0.05). In NL, ANF infusion of 0.10 ig/ kg per min (40 pmol/kg per min) induced increases (P < 0.05) of absolute (from 160±23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
183
2
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 685 publications
(193 citation statements)
references
References 44 publications
7
183
2
1
Order By: Relevance
“…Many studies have detailed the central hemodynamic, arterial, renal, and adrenal effects of exogenous [1][2][3][4][5][6][7][8] and endogenous 9 NPs in animal models of HF 1 and in human HF, 2-9 but little is known about the effects of NPs on the capacitance vasculature in this condition. In the present study, we assessed the effects of all 4 currently known human NPs on the forearm vasculature in matched groups of optimally treated cHF patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have detailed the central hemodynamic, arterial, renal, and adrenal effects of exogenous [1][2][3][4][5][6][7][8] and endogenous 9 NPs in animal models of HF 1 and in human HF, 2-9 but little is known about the effects of NPs on the capacitance vasculature in this condition. In the present study, we assessed the effects of all 4 currently known human NPs on the forearm vasculature in matched groups of optimally treated cHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Hirooka et al 4 and Nakamura et al 6,17 reported reduced forearm resistance-vessel responses to intra-arterial infusion of ANP and BNP (but not CNP) in HF patients versus healthy controls. Interestingly, in these studies, changes in FBF to BNP and CNP were less than those in ANP (on an equimolar basis) in healthy controls, but approximately equipotent in patients with HF.…”
Section: Mechanism Of the Attenuated Forearm Resistance-vessel Responmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends have been observed during ANF infusions by others, 21 sometimes with rebound rise after cessation of ANF. 22 Although ANF has been shown to inhibit corticotropin releasing factor release in hypothalamic cells 23 as well as adrenocorticotropin hormone secretion from pituitary cells, 24 further work is required to clarify such an action of ANF in vivo under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cardiac expression of ANP and BNP and release of this peptides into the circulation is a characteristic feature in heart failure. Despite this elevation, the physiologic response to these peptides is diminished [33,34]. Currently two studies were published describing hyporesponsiveness of cardiac and renal tissues to ANP in congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%